Ab Initio Study of Structural, Electronic, and Hyperfine Properties of n-type SnO2:Ta Semiconductor - Darriba, German Nicolas (2014)
A detailed theoretical first-principles study of structural, electronic, and hyperfine properties at Sn and Ta sites of undoped and Ta-doped rutile SnO2 is presented, using the Full-Potential Augmented Plane Wave plus local orbitals (FP-APW+lo) method. In the Ta-doped systems, we performed calculations for two different charge states. The predicted electric-field-gradient (EFG) tensor, the key magnitude in this study, for both charge states of the impurity result to be almost equal and in good agreement with Time-Differential Perturbed γ–γ Angular Correlation (TDPAC) results in 181Ta-doped SnO2 thin films. This study enables at present to discuss the origin of the EFG and the role played by the structural anisotropic contractions introduced by the Ta atom and the impurity charge state on the hyperfine properties. To determine the correct charge state of the impurity, we performed energetic studies, predicting the metallic behavior of degenerate semiconductors, in agreement with resistivity experimental results obtained in samples with the same Ta dilution.